The Influence Of Internal Control Systems, Government Size, Information Technology And Human Resources On The Transparency Of Regional Government Financial Management: Study On Organizations Kerinci Regency Regional Apparatus (OPD) - Zuska Ega; Yudi Yudi; Yuliusman Yuliusman; Sumarni Sumarni (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the influence of internal control systems, government size, information technology, human resources on the transparency of regional financial management (case study of the Kerinci Regency Regional Apparatus Organization (OP). The population in this study were Civil Servants in 42 OPDs in Kerinci Regency consisting of 42 OPDs. The sample in this study used a saturated sample, namely a sampling technique using the entire population as a research sample consisting of 168 respondents. This research method uses quantitative methods. This research uses primary data obtained from questionnaires distributed to respondents. The research results show that the internal control system has no significant effect on the transparency of regional financial management, while the size of the government has a significant effect on the transparency of regional financial management, while information technology has no significant effect on the transparency of regional financial management and human resources have an effect on the transparency of regional financial management.